Inventário de Odonata imaturo da Ilha de Cotijuba - Belém - Pará - Pereira, Júlia Daniela Braga (Museu Paraense Emílio Goeldi, 2023)
The order Odonata, popularly known as dragonflies or hyacinths, comprises one of the oldest insect orders, existing on the globe since the Upper Carboniferous period. They are amphibious insects with hemimetabolic development, their immatures are aquatic and the adults winged and terrestrial. They have a chewing mouth apparatus and are voracious predators. This study was carried out at Praia da Saudade on Cotijuba Island, where three potentially propitious points were chosen to obtain specimens. Collections were done bimonthly, from August 2003 to April 2004. Adults were collected with entomological nets and immatures with the help of shells and trays, being separated into small glass containers individually for laboratory rearing. The immature specimens were kept alive and fed on Culicidae larvae and pupae. Both immature and adult specimens are being identified with the help of specific keys and identified to the most precise taxon. To date, only two families have been recorded: Libellulidae and Coenagrionidade, with the former accounting for 90% of the total number of individuals collected. In Libellulidae two genera have been identified: Brythemis Hagen,1861 and Micratbyria Kirby 1889; and in the Coenagrionidae family only the genus Enallagma Charpentier, 1840. Some specimens are still being identified. The data obtained are not yet conclusive, however, to date the specimens of Odonata without question have not shown to function as biological controllers under laboratory conditions.